Alkali-activated aluminosilicate sealing system for deep high-temperature well applications. (January 2021) - Kruszewski, Michal; Glissner, Marvin; Hahn, Simon; Wittig, Volker
Highlights: Geopolymer sealant is a potential replacement for Portland cement in HT wells. Geopolymer sealant provides high strength and good resistance towards thermal cyclic loading. Acid insensitivity and high ductility proves application of geopolymers in HT wells. Abstract: This study proposes potential replacement for the Portland-based cement, which is a common sealant used in deep high-temperature geothermal wellbore completions. The experimental laboratory studies were focussed on alkali-activated aluminosilicates. It was proven, that the so-called, geopolymer-based sealing systems exhibit high compressive and flexural strength at elevated temperatures, good resistance towards thermal cyclic loading, high ductility, acid insensitivity, and improved water permeability. Additionally, alkali-activated aluminosilicate sealing systems are economically feasible and their CO2 emission, during the manufacturing process, is significantly lower in comparison with the conventional Portland-based cement types, making them an environmentally friendly option for deep wellbore completions in unconventional high-temperature geothermal systems.